Consistent prokaryotic successional dynamics across contrasting phytoplankton blooms - Gómez-Letona, Markel; Arístegui, Javier; Riebesell, Ulf; Sebastián, Marta (Limnology and Oceanography, 2025)
16 pages, 6 figures, 1 table, supporting Information https://doi.org/10.1002/lno.12773.-- Data availability statement: Flow cytometry (abundances, viability) and BONCAT results are available in the PANGAEA repository (www.pangaea.de) under accession number 964544 (Gómez-Letona et al. 2024). All other ancillary biogeochemical parameters are also available in PANGAEA and/or can be found in their respective publications: Baumann et al. (2021) for inorganic nutrients, PHP, and particulate organic matter; Ortiz et al. (2022b) for Chl a measurements and diatom community composition; Ortiz et al. (2022a) for fractionated Chl a; and Gómez-Letona et al. (2022) for all dissolved organic matter variables. The sequencing data for this study have been deposited in the European Nucleotide Archive at EMBL-EBI (www.ebi.ac.uk/ena) under accession number PRJEB67976 Heterotrophic prokaryotes play a vital role in organic matter cycling in the ocean and have been observed to undergo substrate-controlled successions during phytoplankton blooms. However, there is limited understanding of the succession patterns during blooms triggered by upwelling events of different characteristics. Here we simulated eight upwelling scenarios of varying intensity and duration (single vs. recurring pulses) by adding nutrient-rich mesopelagic waters into large-scale mesocosms containing oligotrophic surface waters from the subtropical North Atlantic. Over a monitoring period of nearly 6 weeks, we observed that phytoplankton blooms displayed diverging outcomes depending on the upwelling mode: treatments with single upwelling pulses presented a unique, short-lived bloom, whereas recurring upwelling resulted in blooms that were sustained over time. Prokaryotic abundances were positively related to upwelling intensity and presented three similar abundance cycles in all treatments, whereas heterotrophic activity differed between the two upwelling modes. The successional dynamics of free-living and particle-associated communities were consistent regardless ...